Preparation method of anti-static plate

By vacuum pressurized immersion, electrochemical treatment and heat treatment of poly3,4-ethylenedioxythiophene/polystyrene sodium sulfonate solution on solid wood floors, an anti-static layer with high conductivity and excellent mechanical properties is formed. The problem of solid wood flooring lacks anti-static performance has achieved its wide application in electrostatic sensitive places.

CN119458546APending Publication Date: 2025-02-18FUJIAN SHUNCHANG SHENG SHENG WOOD IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411431390.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing solid wood floor lacks anti-static properties, which limits its application in places such as precision instrument rooms, computer rooms and dustproof rooms.

Method used

The solution of poly3,4-ethylenedioxythiophene/polystyrene sodium sulfonate was used for vacuum pressurization immersion, followed by electrochemical treatment with 3,4-ethylenedioxythiophene solution and finally heat treatment, so as to Form an antistatic layer with high conductivity and excellent mechanical properties.

Benefits of technology

The prepared anti-static plate has high conductivity and mechanical properties, which can effectively prevent electrostatic discharge. It is suitable for precision instrument rooms, computer rooms, dustproof rooms and other places, and has high economic value and social benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005083770630000051
    Figure BDA0005083770630000051
Patent Text Reader

Abstract

The invention discloses a preparation method of an anti-static plate, and belongs to the technical field of wood functional treatment. The preparation method comprises the following steps: firstly, carrying out vacuum pressure impregnation treatment on a plate by using a poly (3, 4-ethylenedioxythiophene) / sodium polystyrene sulfonate solution, then, carrying out electrochemical treatment on the plate by using a 3, 4-ethylenedioxythiophene solution, and finally, carrying out heat treatment on the plate. The prepared anti-static plate has high conductivity and excellent mechanical properties, can be widely used as anti-static solid wood floors of precise instrument rooms, machine rooms and dustproof rooms, and has high economic value and social benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of wood functionalization treatment, and in particular relates to a method for preparing an antistatic plate. Background Art

[0002] Static electricity is a common physical phenomenon. With the rapid development of integrated circuits and the widespread application of polymer materials in the past decade, the harm caused by the force, discharge and induction of static electricity is very serious. Therefore, precision instrument rooms, computer rooms and dustproof rooms have high requirements for electrostatic protection and must use anti-static floors. Traditional anti-static floors are mainly plastic floors, all-steel floors and aluminum alloy floors. Compared with traditional anti-static floors, solid wood floors are popular because of their advantages such as sound insulation and heat insulation, humidity regulation, warm in winter and cool in summer, and green and harmless. However, solid wood floors are restricted in use because they do not have anti-static functions. Cleverly compounding conductive components and wood is an effective way to prepare green and environmentally friendly anti-static solid wood floors. Poly (3,4-ethylenedioxythiophene) is an important structural conductive polymer material. Because of the special regular and ordered planar molecular structure of poly (3,4-ethylenedioxythiophene) and the electron-donating effect of oxygen atoms in the molecule, doped poly (3,4-ethylenedioxythiophene) is the most stable conductive polymer material known to date. At the same time, poly (3,4-ethylenedioxythiophene) has the characteristics of simple preparation method, uniform film formation, high conductivity and easy regulation of molecular aggregation structure, which provide excellent conditions for the application of poly (3,4-ethylenedioxythiophene) in anti-static solid wood flooring. Summary of the invention

[0003] The present invention aims at the problem that the current solid wood floor has poor antistatic performance, and provides a method for preparing an antistatic board. The antistatic board prepared by the present invention has high conductivity and excellent mechanical properties, can be widely used as antistatic solid wood floor in precision instrument rooms, machine rooms and dustproof rooms, and has high economic value and social benefits.

[0004] To achieve the above object, the present invention adopts the following technical solution:

[0005] A method for preparing an antistatic plate comprises firstly subjecting the plate to vacuum pressure impregnation treatment with a poly(3,4-ethylenedioxythiophene) / sodium polystyrene sulfonate solution, then subjecting the plate to electrochemical treatment with a 3,4-ethylenedioxythiophene solution, and finally subjecting the plate to heat treatment.

[0006] The preparation method of the antistatic plate specifically comprises the following steps:

[0007] (1) placing the dried plate sample in an automatic vacuum pressure tank, evacuating to a vacuum degree of 0.02-0.06 MPa, maintaining the pressure for 30-60 min, injecting a 2-6% by weight poly (3,4-ethylenedioxythiophene) / sodium polystyrene sulfonate aqueous solution, pressurizing to 0.6-1.0 MPa, maintaining the pressure for 30-60 min, and releasing the pressure; after continuing to immerse for 2-4 h at normal pressure, taking out the plate sample, and air-drying at 60° C. for 24 h to obtain a pretreated plate sample;

[0008] (2) Using the pretreated plate sample as the working electrode, the platinum sheet as the counter electrode, the saturated calomel electrode as the reference electrode, and the 3,4-ethylenedioxythiophene solution as the electrolyte, the pretreated plate sample is electrochemically treated by cyclic voltammetry, with a voltage range of 0 to 1.2 V, a scan rate of 10 to 50 mV / s, and a treatment time of 20 to 40 min; the treated plate sample is first air-dried at 60° C. for 12 h, then heated to 100 to 140° C. in a nitrogen atmosphere, kept warm for 0.5 to 2 h, and finally the temperature is lowered to room temperature at a rate of 0.5 to 2° C. / min to obtain the antistatic plate.

[0009] In the 3,4-ethylenedioxythiophene solution, the concentration of 3,4-ethylenedioxythiophene is 0.02-0.1 mol / L, the concentration of p-toluenesulfonic acid is 0.05-0.2 mol / L, and the solvent is deionized water.

[0010] The significant advantages of the present invention are:

[0011] (1) Because wood is an insulating material, it cannot be directly used as a working electrode for electrochemical treatment. Therefore, the present invention first uses a poly (3,4-ethylenedioxythiophene) / sodium polystyrene sulfonate solution to vacuum-pressurize the plate to form a poly (3,4-ethylenedioxythiophene) / sodium polystyrene sulfonate conductive layer on the plate, and then uses the plate as a working electrode, a platinum sheet as a counter electrode, a saturated calomel electrode as a reference electrode, and a 3,4-ethylenedioxythiophene solution as an electrolyte to attach poly (3,4-ethylenedioxythiophene) to the plate by cyclic voltammetry. Compared with the chemical oxidation method, the poly (3,4-ethylenedioxythiophene) prepared by cyclic voltammetry is more uniform and dense, has better conductivity, and can cleverly fill the gaps of the plate. Therefore, by cyclic voltammetry, a uniform and dense poly (3,4-ethylenedioxythiophene) layer with high conductivity can be formed on the surface of the plate, which helps to improve the antistatic performance of the plate.

[0012] (2) Due to the special regular and ordered planar molecular structure of poly (3,4-ethylenedioxythiophene) and the electron-donating effect of oxygen atoms in the molecule, doped poly (3,4-ethylenedioxythiophene) has outstanding environmental stability and electrochemical stability, and is the most stable conductive polymer material known to date. However, due to the fast electrochemical polymerization reaction rate, the planar molecular structure of the generated poly (3,4-ethylenedioxythiophene) is not regular and orderly, which greatly affects the improvement of the conductivity of poly (3,4-ethylenedioxythiophene). When poly (3,4-ethylenedioxythiophene) is heat-treated, the planar molecular structure of poly (3,4-ethylenedioxythiophene) tends to be regular and orderly when heated, which is conducive to improving the conductivity of poly (3,4-ethylenedioxythiophene).

[0013] (3) The antistatic sheet prepared by the present invention has high conductivity and excellent mechanical properties, and the surface resistivity of the horizontal and vertical lines is 5.27-8.53Ω / cm 2 and 4.95~8.48Ω / cm 2 The flexural strength is 63.2~66.7MPa, and the abrasion value is 0.887~0.951g / 100r. It can be widely used as anti-static solid wood flooring in precision instrument rooms, computer rooms and dust-proof rooms, with high economic value and social benefits. DETAILED DESCRIPTION

[0014] The advantages and effects of the technical solution of the present invention are further described below through several groups of embodiments and comparative examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0015] Example 1

[0016] (1) The dried plate sample is placed in an automatic vacuum pressure tank, evacuated to a vacuum degree of 0.04 MPa, maintained at pressure for 45 minutes, and then injected with a 4% by weight poly (3,4-ethylenedioxythiophene) / sodium polystyrene sulfonate aqueous solution, pressurized to 0.8 MPa, maintained at pressure for 45 minutes, and then released; after continuing to immerse for 3 hours at normal pressure, the plate sample is taken out and air-dried at 60°C for 24 hours to obtain a pretreated plate sample;

[0017] (2) The pretreated plate sample is used as the working electrode, the platinum sheet is used as the counter electrode, the saturated calomel electrode is used as the reference electrode, and the 3,4-ethylenedioxythiophene solution is used as the electrolyte. The pretreated plate sample is electrochemically treated by cyclic voltammetry. The voltage range is 0-1.2V, the scanning rate is 30mV / s, and the treatment time is 30min. The treated plate sample is first air-dried at 60°C for 12h, then heated to 120°C in a nitrogen atmosphere, kept warm for 1h, and finally the temperature is lowered to room temperature at a rate of 1°C / min to obtain the antistatic plate.

[0018] In the 3,4-ethylenedioxythiophene solution, the concentration of 3,4-ethylenedioxythiophene is 0.05 mol / L, the concentration of p-toluenesulfonic acid is 0.1 mol / L, and the solvent is deionized water.

[0019] Example 2

[0020] (1) Place the dried plate sample in an automatic vacuum pressure tank, evacuate to a vacuum degree of 0.02 MPa, maintain the pressure for 30 minutes, inject a 2% by weight poly (3,4-ethylenedioxythiophene) / sodium polystyrene sulfonate aqueous solution, pressurize to 0.6 MPa, maintain the pressure for 60 minutes, and release the pressure; continue to immerse for 2 hours at normal pressure, take out the plate sample, and air-dry at 60°C for 24 hours to obtain a pretreated plate sample;

[0021] (2) The pretreated plate sample is used as the working electrode, the platinum sheet is used as the counter electrode, the saturated calomel electrode is used as the reference electrode, and the 3,4-ethylenedioxythiophene solution is used as the electrolyte. The pretreated plate sample is electrochemically treated by cyclic voltammetry. The voltage range is 0-1.2V, the scanning rate is 10mV / s, and the treatment time is 20min. The treated plate sample is first air-dried at 60°C for 12h, then heated to 100°C in a nitrogen atmosphere, kept warm for 2h, and finally the temperature is lowered to room temperature at a rate of 0.5°C / min to obtain the antistatic plate.

[0022] In the 3,4-ethylenedioxythiophene solution, the concentration of 3,4-ethylenedioxythiophene is 0.02 mol / L, the concentration of p-toluenesulfonic acid is 0.05 mol / L, and the solvent is deionized water.

[0023] Example 3

[0024] (1) Place the dried plate sample in an automatic vacuum pressure tank, evacuate to a vacuum degree of 0.06 MPa, maintain the pressure for 60 minutes, inject a 6% by weight poly (3,4-ethylenedioxythiophene) / sodium polystyrene sulfonate aqueous solution, pressurize to 1.0 MPa, maintain the pressure for 30 minutes, and release the pressure; after continuing to immerse for 4 hours at normal pressure, take out the plate sample, air-dry at 60°C for 24 hours, and obtain a pretreated plate sample;

[0025] (2) The pretreated plate sample is used as the working electrode, the platinum sheet is used as the counter electrode, the saturated calomel electrode is used as the reference electrode, and the 3,4-ethylenedioxythiophene solution is used as the electrolyte. The pretreated plate sample is electrochemically treated by cyclic voltammetry. The voltage range is 0-1.2V, the scanning rate is 50mV / s, and the treatment time is 40min. The treated plate sample is first air-dried at 60°C for 12h, then heated to 140°C in a nitrogen atmosphere, kept warm for 0.5h, and finally the temperature is lowered to room temperature at a rate of 2°C / min to obtain the antistatic plate.

[0026] In the 3,4-ethylenedioxythiophene solution, the concentration of 3,4-ethylenedioxythiophene is 0.1 mol / L, the concentration of p-toluenesulfonic acid is 0.2 mol / L, and the solvent is deionized water.

[0027] Comparative Example 1

[0028] The dried board sample was placed in an automatic vacuum pressure tank, evacuated to a vacuum degree of 0.04 MPa, maintained at pressure for 45 minutes, and then injected with a 4% by weight poly (3,4-ethylenedioxythiophene) / sodium polystyrene sulfonate aqueous solution, pressurized to 0.8 MPa, maintained at pressure for 45 minutes, and then released; after continuing to immerse for 3 hours at normal pressure, the board sample was taken out and air-dried at 60°C for 24 hours to obtain a finished product.

[0029] Comparative Example 2

[0030] (1) The dried plate sample is placed in an automatic vacuum pressure tank, evacuated to a vacuum degree of 0.04 MPa, maintained at pressure for 45 minutes, and then injected with a 4% by weight poly (3,4-ethylenedioxythiophene) / sodium polystyrene sulfonate aqueous solution, pressurized to 0.8 MPa, maintained at pressure for 45 minutes, and then released; after continuing to immerse for 3 hours at normal pressure, the plate sample is taken out and air-dried at 60°C for 24 hours to obtain a pretreated plate sample;

[0031] (2) The pretreated plate sample was used as the working electrode, the platinum sheet was used as the counter electrode, the saturated calomel electrode was used as the reference electrode, and the 3,4-ethylenedioxythiophene solution was used as the electrolyte. The pretreated plate sample was electrochemically treated by cyclic voltammetry. The voltage range was 0-1.2 V, the scanning rate was 30 mV / s, and the treatment time was 30 min. The treated plate sample was air-dried at 60°C for 24 h to obtain the finished product.

[0032] In the 3,4-ethylenedioxythiophene solution, the concentration of 3,4-ethylenedioxythiophene is 0.05 mol / L, the concentration of p-toluenesulfonic acid is 0.1 mol / L, and the solvent is deionized water.

[0033] Comparative Example 3

[0034] The dried plate sample is placed in an automatic vacuum pressure tank, evacuated to a vacuum degree of 0.04MPa, and after maintaining the pressure for 45 minutes, a 4% by weight poly (3,4-ethylenedioxythiophene) / sodium polystyrene sulfonate aqueous solution is injected, pressurized to 0.8MPa, maintained for 45 minutes, and then released; after continuing to immerse for 3 hours at normal pressure, the plate sample is taken out, air-dried at 60°C for 12 hours, and then heated to 120°C in a nitrogen atmosphere, kept warm for 1 hour, and finally the temperature is lowered to room temperature at a rate of 1°C / min to obtain a finished product.

[0035] The board samples prepared in the three groups of embodiments and the three groups of comparative examples were tested for conductivity according to the literature (Wang Lijuan, Li Jian, Gu Sijing; Preparation and characterization of polypyrrole / wood veneer conductive composite materials, Functional Materials, 2007, 38 (A08): 3067-3070), tested for flexural strength according to GB / T1936.1-2009, and tested for wear resistance according to GB / T 15036.2-2018. The performance test results are shown in Table 1.

[0036] Table 1 Performance test results

[0037]

[0038] It can be seen from the test results of the three groups of embodiments and the three groups of comparative examples that the plates prepared by the three groups of embodiments have higher conductivity and better mechanical properties, which means that by first subjecting the plates to vacuum pressure impregnation treatment with a poly (3,4-ethylenedioxythiophene) / sodium polystyrene sulfonate solution, then subjecting the plates to electrochemical treatment with a 3,4-ethylenedioxythiophene solution, and finally subjecting the plates to heat treatment, an antistatic plate with higher conductivity and better mechanical properties can be obtained.

[0039] The above description shows and describes the preferred embodiments of the present invention. As mentioned above, it should be understood that the present invention is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the invention concept described herein through the above teachings or the technology or knowledge of the relevant field. The changes and modifications made by those skilled in the art do not depart from the spirit and scope of the present invention, and should be within the scope of protection of the claims attached to the present invention.

Claims

1. A method for preparing an antistatic sheet, characterized in that: Firstly, the plate is subjected to vacuum pressure impregnation treatment with a poly(3,4-ethylenedioxythiophene) / sodium polystyrene sulfonate) solution, then the plate is subjected to electrochemical treatment with a 3,4-ethylenedioxythiophene solution, and finally the plate is subjected to heat treatment; specifically, the following steps are included: (1) placing the dried plate sample in an automatic vacuum pressure tank, evacuating to a vacuum degree of 0.02-0.06 MPa, maintaining the pressure for 30-60 min, injecting a 2-6% by weight poly (3,4-ethylenedioxythiophene) / sodium polystyrene sulfonate aqueous solution, pressurizing to 0.6-1.0 MPa, maintaining the pressure for 30-60 min, and releasing the pressure; after continuing to immerse for 2-4 h at normal pressure, taking out the plate sample, and air-drying at 60° C. for 24 h to obtain a pretreated plate sample; (2) Using the pretreated plate sample as the working electrode, the platinum sheet as the counter electrode, the saturated calomel electrode as the reference electrode, and the 3,4-ethylenedioxythiophene solution as the electrolyte, the pretreated plate sample is electrochemically treated by cyclic voltammetry, with a voltage range of 0 to 1.2 V, a scan rate of 10 to 50 mV / s, and a treatment time of 20 to 40 min; the treated plate sample is first air-dried at 60° C. for 12 h, then heated to 100 to 140° C. in a nitrogen atmosphere, kept warm for 0.5 to 2 h, and finally the temperature is lowered to room temperature at a rate of 0.5 to 2° C. / min to obtain the antistatic plate.

2. The method for preparing the antistatic sheet material according to claim 1, characterized in that: In the 3,4-ethylenedioxythiophene solution, the concentration of 3,4-ethylenedioxythiophene is 0.02-0.1 mol / L, the concentration of p-toluenesulfonic acid is 0.05-0.2 mol / L, and the solvent is deionized water.